Refractory Scedosporium apiospermum Keratitis Successfully Treated with Combination of Amphotericin B and Voriconazole. (20th February 2013) - Fadzillah, Mohd-Tahir; Ishak, Siti-Raihan; Ibrahim, Mohtar
Abstract : Aim . To report a case of refractory fungal keratitis caused by Scedosporium apiospermum . Methods . Interventional case report. Results . A 47-year-old Malay housewife presented with left eye cornea ulcer as her first presentation of diabetes mellitus. There was no history of ocular trauma, contact lens used, or cornea foreign body. Scedosporium apiospermum was isolated from the cornea scrapping. Her cornea ulcer initially responded well to topical Amphotericin B within 3 days but subsequently worsened. Repeat cornea scrapping also yields Scedosporium apiospermum . This refractory keratitis was successfully treated with a combination of topical Amphotericin B and Voriconazole over 6 weeks. Conclusion . Scedosporium apiospermum keratitis is an opportunistic infection, which is difficult to treat despite tight control of diabetes mellitus and intensive antifungal treatment. The infection appeared to have very quick onset but needed long duration of treatment to completely heal. Surgical debridement always plays an important role as a therapeutic procedure as well as establishes the diagnosis through repeat scrapping.